2020
DOI: 10.1007/s00468-020-01954-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of multifunctional laccase gene family in Eucalyptus grandis: potential targets for lignin engineering and stress tolerance

Abstract: Key message A survey of the Eucalyptus grandis genome revealed the presence of 54 laccase genes. Their tissue-specific and stress-induced expression patterns suggest a role in lignification and adaptation to abiotic stresses. Abstract Laccases are multicopper oxidases that play important roles in the oxidation of monolignols during lignin biosynthesis and are reported to be functionally involved in plant development and stress responses. In this study, a genome-wide survey of the Eucalyptus grandis genome reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…Protease-associated (PA) RING/U-box zinc finger family proteins are involved in protein coding, protein–protein interaction, and trafficking of soluble proteins through subcellular compartments [ 90 ]. SKS5 belongs to a gene family ( SKU5-similar ) related structurally to the multiple-copper oxidases, ascorbate oxidase, and laccase, which playing vital roles in lignin biosynthesis, plant development, and stress responses [ 91 ]. What is more, SKU5 and its homologs was reported to be involved in directional root growth by participating in cell wall expansion and synthesis [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protease-associated (PA) RING/U-box zinc finger family proteins are involved in protein coding, protein–protein interaction, and trafficking of soluble proteins through subcellular compartments [ 90 ]. SKS5 belongs to a gene family ( SKU5-similar ) related structurally to the multiple-copper oxidases, ascorbate oxidase, and laccase, which playing vital roles in lignin biosynthesis, plant development, and stress responses [ 91 ]. What is more, SKU5 and its homologs was reported to be involved in directional root growth by participating in cell wall expansion and synthesis [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rice, at least fifteen of the 30 LACs were predicted as the potential targets of miR397, and several of them (such as OsLAC3, OsLAC6, OsLAC7, and OsLAC19) were confirmed in the Indica line O. nivara by degradome analysis (Swetha et al 2018). In Eucalyptus grandis, 17 LAC genes were predicted as the target genes of miR397, among which LAC1, LAC4, LAC10, LAC11, LAC12 and LAC20 were highly expressed in xylem and involved in the biosynthesis of xylem lignin and maintaining mechanical toughness of stems (Arcuri et al 2020). In pears, 27 LAC genes identified from genomic sequences were potential target genes of PbrmiR397a (Xue et al 2019).…”
Section: Target Genes Of Mir397mentioning
confidence: 95%
“…Laccase has been recognized in the lignification process through the oxidation of lignin precursors. Indeed, Arcuri et al [26] demonstrated involvement of LACCASE genes in lignification as a response to adaptation to abiotic stresses in Eucalyptus.…”
Section: Discussionmentioning
confidence: 99%